Case Report: Tonsilitis Kronik Pada Anak Usia 12 Tahun - Retno Mareintika; Graharti, Risti; Hayati, Rina (Medula, 2025)
Chronic tonsillitis is one of the most common upper respiratory tract infections in children. This condition is characterized by recurrent inflammation of the tonsils, which can interfere with daily activities, reduce appetite, impair sleep quality, and increase the risk of severe complications such as peritonsillar abscess, parapharyngeal abscess, or sepsis. Appropriate management is essential to prevent recurrence and further complications.This case report describes a 12-year-old female patient who presented with complaints of odynophagia, a foreign body sensation in the throat, halitosis, recurrent fever, and snoring during sleep. Physical examination revealed T3–T3 tonsils with enlarged crypts and the presence of detritus, leading to a diagnosis of chronic tonsillitis or recurrent acute tonsillitis. Initial management included amoxicillin 500 mg three times daily for 10 days, paracetamol 10–15 mg/kgBW as needed for fever, and an antiseptic mouthwash. The patient and her family were also educated on medication adherence, maintaining oral hygiene, and avoiding triggering foods such as spicy meals, cold drinks, and unhygienic snacks.Conservative therapy provided temporary symptomatic improvement; however, considering the recurrent episodes and sleep disturbances, the patient was advised to undergo tonsillectomy as definitive therapy. This case emphasizes that chronic tonsillitis in children requires accurate diagnosis, comprehensive management, and timely intervention. Conservative treatment may alleviate symptoms, but tonsillectomy plays a pivotal role in preventing recurrence, reducing the risk of complications, and improving the patient’s quality of life.